2014
DOI: 10.1021/ja501859w
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Highly Responsive pH Sensors Based on DNA i-Motif

Abstract: Availability of strategies for molecular biosensing over a finely adjustable dynamic range is essential for understanding and controlling vital biological processes. Herein we report design principles of highly responsive pH sensors based on a DNA i-motif where both response sensitivity and transition midpoint can be tuned with high precision over the physiologically relevant pH interval. The tuning is accomplished via rational manipulations of an i-motif structure as well as incorporation of allosteric contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
140
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 37 publications
2
140
0
Order By: Relevance
“…4 obtained for separate solutions method. Moreover, our results demonstrated that the manipulation of an i-motif composition can lead to the development of pH sensors with a specifically defined transition midpoint (precision of 0.1 pH units) and a good response resolution (0.2 pH units or better), which agrees with the results for FRET pH sensor based on similar design platform recently reported by Nesterov et al [27]. It is worth mention that we performed preliminary experiments [28] to check if the pHSO_A sensor could sense pH change in a living cell.…”
Section: Resultssupporting
confidence: 91%
“…4 obtained for separate solutions method. Moreover, our results demonstrated that the manipulation of an i-motif composition can lead to the development of pH sensors with a specifically defined transition midpoint (precision of 0.1 pH units) and a good response resolution (0.2 pH units or better), which agrees with the results for FRET pH sensor based on similar design platform recently reported by Nesterov et al [27]. It is worth mention that we performed preliminary experiments [28] to check if the pHSO_A sensor could sense pH change in a living cell.…”
Section: Resultssupporting
confidence: 91%
“…[ 19 ] Molecular pH sensors that function over a broad pH range are particularly useful but challenging to design and as a result most function under either predominantly acidic or basic conditions. [ 20 ] We observed broad spectrum pH sensitivity of material (1) between pH 4 and pH 10 the solutions emit variations of white light with the strongest intensity at neutral pH; (2) a switch from blue to cyan emission is observed for solutions at pH < 4; (3) blue emitting solutions are formed at pH > 10 ( Figure 4 and Figure S9, Supporting Information). At pH 3 and below, all emission bands are dramatically reduced, indicative of general dissociation of metal-ligand bonds due to protonation of the pyridyl coordination site (pKa [H2Tpy]2+ = 3.57, pKa [HTpy]+ = 4.54).…”
Section: Communicationmentioning
confidence: 88%
“…These include sequence-dependency limitations (only C-rich sequences with a certain consecutive content of cytosines can form i-motif), structural constraints (formation of the complete tertiary structure is required in order to allow a pH-control), and a limited and quite narrow pH dynamic range (this usually spans not more than 2 orders of magnitude). 52,53 In response to the above limitations the use of triplexforming domains as an additional tool to control reactions in DNA-based nanotechnology can provide several advantages. For example, although homopurine sequences are needed to form triplex structures, the sequence-dependent limitations of our approach are far less strict than those related to the use of imotifs.…”
Section: Nano Lettersmentioning
confidence: 99%